A Galerkin finite element method to solve fractional diffusion and fractional diffusion-wave equations - Esen, Alaattin; Ucar, Yusuf; Yagmurlu, Nuri; Tasbozan, Orkun (Mathematical Modelling and Analysis, 2013)
In the present study, numerical solutions of the fractional diffusion and fractional diffusion-wave equations where fractional derivatives are considered in the Caputo sense have been obtained by a Galerkin finite element method using quadratic B-spline base functions. For the fractional diffusion equation, the L1 discretizaton formula is applied, whereas the L2 discretizaton formula is applied for the fractional diffusion-wave equation. The error norms L 2 and L ∞ are computed to test the accuracy of the proposed method. It is shown that the present scheme is unconditionally stable by applying a stability analysis to the approximation obtained by the proposed scheme.